Lancet doors and windows having pointed arch at the top - Mumbai Archive Project (Jio Institute, 2024)
The lancet doors and windows have a distinctive pointed arch at the top. The windows feature fine tracery. Tracery is typically used as a decorative element in the upper part of Gothic windows (or screens, panels, and vaults), which are divided into sections of various proportions by a stone framework (wooden in this case).